1977
DOI: 10.2307/481388
|View full text |Cite
|
Sign up to set email alerts
|

The Valley de Naco: Ethnohistory and Archaeology in Northwestern Honduras

Abstract: Each copy of any part of a JSTOR transmission must contain the same copyright notice that appears on the screen or printed page of such transmission. JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…At the time of the Spanish Conquest, it was occupied by peoples speaking Chort¡ Maya, Nahuat, Care, Lenca, and Jicaque (Feldman 1987). Henderson (1977) has suggested that the Sula plain formed a linguistic frontier between Chol and Jicaque speakers at this time. A wide variety of settlement and artifactual data indicate that it was not integrated into a single unit or polity, and several culturally and linguistically distinct groups may have lived side-by-side during the Late Postclassic and Contact periods (Henderson 1978).…”
Section: Costa Rica and Nicaraguamentioning
confidence: 97%
See 2 more Smart Citations
“…At the time of the Spanish Conquest, it was occupied by peoples speaking Chort¡ Maya, Nahuat, Care, Lenca, and Jicaque (Feldman 1987). Henderson (1977) has suggested that the Sula plain formed a linguistic frontier between Chol and Jicaque speakers at this time. A wide variety of settlement and artifactual data indicate that it was not integrated into a single unit or polity, and several culturally and linguistically distinct groups may have lived side-by-side during the Late Postclassic and Contact periods (Henderson 1978).…”
Section: Costa Rica and Nicaraguamentioning
confidence: 97%
“…Ethnohistoric documents describe coastwise trade routes from southern Campeche around the Yucatan Peninsula to the Gulf of Honduras and along the Caribbean coast of Central America. Cort‚s obtained information from the merchants of Xicalango, on the Laguna de T‚rminos, and Acal n, on the R¡o Candelaria, about major coastal settlements along most of the Caribbean coast of Central America and a map showing the route from the Laguna de T‚rminos to Nito and Naco in northwestern Honduras and centers in coastal Nicaragua and Panama (Henderson 1977).…”
Section: Costa Ricamentioning
confidence: 99%
See 1 more Smart Citation
“…Our interest has been in understanding this social formation, to provide an alternative to more common models of societies in which pronounced social hierarchy developed in the presence of sufficient resources and time. The lower Ulúa Valley had an abundance of well‐drained, fertile soils (Pope 1987); was historically a center of the production of cacao (Bergmann 1969; Henderson 1979), one of the major cash crops in prehispanic times; exported not only cacao but also other valuables to Maya cities in Yucatan in the sixteenth century (Henderson 1979); and in earlier prehispanic times produced a rich material culture, some of it exported, that required the support of a wide array of artisans (Lopiparo 2006; Luke and Tykot 2007).…”
Section: Puerto Escondido: a History Of Placementioning
confidence: 99%
“…The inhabitants of the region probably included speakers of several languages: Maya (the Chol and possibly Chorti variants), Jicaque (possibly a member of the Hokan family, a tongue primarily associated with the Honduran north coast east of the Ulua), and Lenca (a language or group of languages of controversial affinity, distributed throughout western Honduras from south of Naco to the Pacific coast) (Campbell 1976;Chapman 1958;Scholes and Roys 1948:17). There is no direct evidence for the native language(s) spoken in Naco itself, although the most likely candidates would seem to be Lenca and Maya (Chapman 1978b;Henderson 1979;J.E.S. Thompson 1970:86, 91-92, 130).…”
Section: Nolasco Bichrome-synchronic Perspectivementioning
confidence: 99%